Acceptability of vaginal self-sampling with high-risk human papillomavirus testing for cervical cancer screening: a French questionnaire-based study. Issue 1 (2nd January 2021) - Bertucci, Martina; Bonnet, Emmanuel; Satger, Laura; Kreiche, Antoine; Chappert, Jean-Loup; Loy-Morel, Silvia; Segondy, Michel; Daurès, Jean Pierre; Boulle, Nathalie
ABSTRACT: In France, cervical cancer screening based on cervical smear has a participation rate of around 60%. New screening strategies are encouraged to increase the participation of under-screened women, including vaginal self-sampling with high-risk human papillomavirus (HR-HPV) testing. This study was based on the distribution of an anonymous self-administered questionnaire to assess the acceptability of vaginal self-sampling with HR-HPV testing by women aged 25 to 65 years in two French Departments of the South of France, Aude, and Hérault, showing low participation in cervical cancer screening. Factors influencing this acceptability were also analyzed. From May to July 2017, 349 completed questionnaires were collected. Women declared high acceptability for vaginal self-sampling (81%) preferably at home (82.6%). Acceptability was statistically higher in the Department of Herault ( p = .001) and for women older than 50 years ( p = .018). There was no difference according to educational level or attendance to cervical cancer screening. Knowledge about cervical cancer and cervical cancer screening was significantly influenced by educational level. This study confirmed that vaginal self-sampling with HR-HPV testing was highly accepted, including by under-screened women, encouraging further interventional studies. Education about cervical cancer and cervical cancer screening should be part of these programs, especially for women with lower educational level.